What value of x makes the equation 3(x - 6) - 8x = -2 + 5(2x + 1) true?
3(x - 6) - 8x = -2 + 5(2x + 1) 3x - 18 - 8x = -2 + 10x + 5 -5x - 18 = 10x + 3 -5x - 10x = 3 + 18 -15x = 21 x = 21-/15 x = -21/15 x = -7/5
Question
Updated 12/15/2017 5:33:49 AM
Edited by Masamune [12/15/2017 5:31:40 AM]
Rating
3
3(x - 6) - 8x = -2 + 5(2x + 1)
3x - 18 - 8x = -2 + 10x + 5
-5x - 18 = 10x + 3
-5x - 10x = 3 + 18
-15x = 21
x = 21-/15
x = -21/15
x = -7/5

29,769,321
*
Get answers from Weegy and a team of really smart live experts.
S
L
R
R
Points 2112 [Total 3627] Ratings 12 Comments 602 Invitations 139 Offline
S
L
Points 1501 [Total 1501] Ratings 7 Comments 1411 Invitations 2 Offline
S
L
P
C
P
C
P
C
L
Points 1424 [Total 5220] Ratings 6 Comments 1364 Invitations 0 Offline
S
L
R
Points 1135 [Total 1772] Ratings 10 Comments 435 Invitations 60 Offline
S
L
Points 659 [Total 1099] Ratings 3 Comments 609 Invitations 2 Offline
S
L
Points 555 [Total 2672] Ratings 5 Comments 505 Invitations 0 Offline
S
L
1
P
1
Points 370 [Total 1819] Ratings 14 Comments 230 Invitations 0 Offline
S
L
Points 207 [Total 553] Ratings 11 Comments 37 Invitations 6 Offline
S
L
Points 203 [Total 696] Ratings 6 Comments 123 Invitations 2 Offline
S
L
Points 189 [Total 199] Ratings 0 Comments 179 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.